Design of the Dutch Obesity Intervention in Teenagers (NRG-DOiT): systematic development, implementation and evaluation of a school-based intervention aimed at the prevention of excessive weight gain in adolescents - Brug Johannes (BMC Public Health, 2006)
Abstract Background Only limited data are available on the development, implementation, and evaluation processes of weight gain prevention programs in adolescents. To be able to learn from successes and failures of such interventions, integral written and published reports are needed. Methods Applying the Intervention Mapping (IM) protocol, this paper describes the development, implementation, and evaluation of the Dutch Obesity Intervention in Teenagers (DOiT), a school-based intervention program aimed at the prevention of excessive weight gain. The intervention focussed on the following health behaviours: (1) reduction of the consumption of sugar-sweetened beverages, (2) reduction of energy intake derived from snacks, (3) decrease of levels of sedentary behaviour, and (4) increase of levels of physical activity (i.e. active transport behaviour and sports participation). The intervention program consisted of an individual classroom-based component (i.e. an educational program, covering 11 lessons of both biology and physical education classes), and an environmental component (i.e. encouraging and supporting changes at the school canteens, as well as offering additional physical education classes). We evaluated the effectiveness of the intervention program using a randomised controlled trial design. We assessed the effects of the intervention on body composition (primary outcome measure), as well as on behaviour, behavioural determinants, and aerobic fitness (secondary outcome measures). Furthermore, we conducted a process evaluation. Discussion The development of the DOiT-intervention resulted in a comprehensive school-based weight gain prevention program, tailored to the needs of Dutch adolescents from low socio-economic background.